2018
DOI: 10.1016/j.brat.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized controlled platform trial comparing group MEmory specificity training (MEST) to group psychoeducation and supportive counselling (PSC) in the treatment of recurrent depression

Abstract: Impaired ability to recall specific autobiographical memories is characteristic of depression, which when reversed, may have therapeutic benefits. This cluster-randomized controlled pilot trial investigated efficacy and aspects of acceptability, and feasibility of MEmory Specificity Training (MEST) relative to Psychoeducation and Supportive Counselling (PSC) for Major Depressive Disorder (N = 62). A key aim of this study was to determine a range of effect size estimates to inform a later phase trial. Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 35 publications
2
51
1
Order By: Relevance
“…As such, one might question the extent to which our sample corresponds with other groups of depressed participants. The mean BDI‐II score of our participants with depression was similar to that from other studies in this area involving depressed participants (Eigenhuis, Seldenrijk, van Schaik, Raes, & van Oppen, ; Neshat Doost et al ., ; Raes, Williams, et al ., ; Werner‐Seidler et al ., ) so it is unlikely that our sample is exceptionally severe. Nevertheless, future research could examine the contribution of these variables to the observed effects by comparing samples of depressed participants that are medication naïve or not, who do or do not possess comorbidities or between in‐ and out‐patients.…”
Section: Discussionmentioning
confidence: 98%
“…As such, one might question the extent to which our sample corresponds with other groups of depressed participants. The mean BDI‐II score of our participants with depression was similar to that from other studies in this area involving depressed participants (Eigenhuis, Seldenrijk, van Schaik, Raes, & van Oppen, ; Neshat Doost et al ., ; Raes, Williams, et al ., ; Werner‐Seidler et al ., ) so it is unlikely that our sample is exceptionally severe. Nevertheless, future research could examine the contribution of these variables to the observed effects by comparing samples of depressed participants that are medication naïve or not, who do or do not possess comorbidities or between in‐ and out‐patients.…”
Section: Discussionmentioning
confidence: 98%
“…Research to-date suggests that MeST may hold promise as an intervention within depression. In particular, MeST ameliorates rAMS and affects associated symptoms and psychological processes [15,16,20]. However, until now, MeST has been confined to research settings and for its potential clinical utility to be realised, it is critical to demonstrate that it has comparable effects when transported to routine clinical practices where depressed patients in the community would typically access treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A mean of pre-post difference scores is calculated per setting. A 95% CI is calculated for the total sample by using a pooled SD of the pre-intervention scores (a mean difference of 2.70 on the AMT, 95% CI [1.90-3.50]) with a previous study with high internal validity which used the same inclusion criterion [20] in which participants increased from a mean of 5.2 (SE = 0.4) to a mean of 8.0 (SE = 0.4), shows that the adaptations made for RCPs here did not decrease the efficacy of MeST in a significant way. Also, a translation to an open version (with a mean difference ranging from 2.33 to 3.42 in Settings 1, 2 and 3; see Table 5) showed comparably strong effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of these reviews reported that no studies have yet examined the impact of a memory‐therapeutic intervention among people with BD. One intervention, Memory Specificity Training (MeST) (Raes, Williams, et al, ), is regarded as a promising method for improving memory specificity and remediating related symptoms and processes in UD (Eigenhuis, Seldenrijk, Schaik, Raes, & Oppen, ; Raes, Williams, et al, ; Werner‐Seidler et al, ), PTSD (Maxwell et al, ), and Schizophrenia (Blairy et al, ; Ricarte, Hernández‐Viadel, Latorre, & Ros, ). A recent meta‐analysis confirms these effects (Barry et al, ) and concluded that MeST has also been found to improve other processes associated with rAMS, such as deficits in problem solving, future‐oriented thinking, and hopelessness.…”
Section: Introductionmentioning
confidence: 99%